Peran Pemerintah Daerah dalam Pelaksanaan Sertifikasi Wakaf berdasarkan Undang-Undang Nomor 41 Tahun 2004 tentang Wakaf di Kabupaten Bondowoso - Anisatul Hamidah (Fakultas Hukum Universitas Islam Jember, 2017)
One of the obstacles in perwakafan is the number of wakaf land to religious institutions that currently have not done the process of certification of wakaf in accordance with Law number 41 of 2004 on waqf. the fact posed a problem for the people who use the wakaf land, among others, the society is less comfortable and calm in worship because of the unclear status of the land of religious institutions used for religious activities of the community. Departing from the problem Bondowoso district government has initiated to accelerate the process of land certification of waqf by cooperating with various parties such as Ministry of Religious Affairs, National Land Board, Indonesian Mosque Council, Representative of Indonesian Waqf Board, Waqf Institution and Nahdlatul Ulama Land and others , in the hope that the certification process of wakaf land in Bondowoso Regency can run maximally.